1997
DOI: 10.1002/(sici)1099-1379(199709)18:5<415::aid-job813>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

When success breeds failure: the role of self-efficacy in escalating commitment to a losing course of action

Abstract: The search for individual dierences relevant to behavior in escalation situations has met with little success. Continuing the search, this study investigated self-ecacy judgments as a potentially important individual dierence in escalating commitment to a losing course of action. Predictions derived from self-ecacy theory suggest that selfpercepts of high ecacy would exacerbate the economically irrational escalation bias whereas self-percepts of low ecacy would diminish it. These predictions were consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
98
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 68 publications
8
98
0
5
Order By: Relevance
“…However, venture capitalists have reported that serial entrepreneurs are actually less able to recognize their own limitations than first-time entrepreneurs (Wright et al, 1997b). More generally, Whyte et al (1997) found that individuals with high levels of self-efficacy with regard to risk taking were more likely to escalate commitment to a losing course of action.…”
Section: Individual Factors Associated With Overconfidencementioning
confidence: 99%
“…However, venture capitalists have reported that serial entrepreneurs are actually less able to recognize their own limitations than first-time entrepreneurs (Wright et al, 1997b). More generally, Whyte et al (1997) found that individuals with high levels of self-efficacy with regard to risk taking were more likely to escalate commitment to a losing course of action.…”
Section: Individual Factors Associated With Overconfidencementioning
confidence: 99%
“…Such beliefs may also affect the degree to which entrepreneurial investments are perceived to be sunk and the extent to which individuals escalate their commitment of investment in venturing when the objective likelihood of success is low. For example, there is some evidence suggesting that self-efficacy and confidence is associated with greater commitment of resources in settings that are highly risky or highly likely to be a losing course of action (McCarthy et al, 1993;Whyte, Saks, & Hook, 1997). While we show greater self-efficacy is associated with greater entrepreneurial investment, given our research design, we cannot determine whether this is also an inappropriate over-commitment of resources to the startup activity.…”
Section: Implications For Theory and Practicementioning
confidence: 99%
“…galais und Moser (2001) fanden beispielsweise, dass mit ihrer derzeitigen Arbeitssituation unzufriedene Auszubildende dann weniger an einen Abbruch ihrer Ausbildung dachten, wenn sie generell zu mehr Optimismus neigten. Hohe Selbstwirksamkeit, ein Konstrukt, das mit Optimismus stark korreliert ist, geht ebenfalls mit der neigung zu eskalierendem Commitment einher (Whyte, Saks & Hook, 1997).…”
Section: Tabelleunclassified